1940
DOI: 10.1002/recl.19400590708
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on a synthesis of dl‐pelletierine. I

Abstract: The root bark of the pomegranate tree (Punica Granafum L.) was first investigated by T a n r e t I ) , who isolated from it several alkaloids, which were named by him pelletierine, Y -pelletierine, methylpelletierine and isopelletierine in honour of the French alkaloid chemist, P e 1 1 e t i e r. Two of T a n r e t ' s alkaloids, pelletierine and methylpelletierine, were optically active: in that respect alone the former difEered from isopelletierine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1950
1950
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Examples involving even stronger bases than employed here include the use of Na or K to promote dark red and deep purple coloration in 4-methylpyridine and 4-propylpyridine, respectively 16) . With phenyllithium as base 17) , colourless 2-methylpyridine develops exactly the same colour as observed in the present experiments. Similarly, in the matrix polymerization of 4-vinylpyridine (4VP) on polyphosphates and subsequent hydrolysis and treatment of hydrolysate with aq.…”
Section: -Suggested Explanationssupporting
confidence: 80%
“…Examples involving even stronger bases than employed here include the use of Na or K to promote dark red and deep purple coloration in 4-methylpyridine and 4-propylpyridine, respectively 16) . With phenyllithium as base 17) , colourless 2-methylpyridine develops exactly the same colour as observed in the present experiments. Similarly, in the matrix polymerization of 4-vinylpyridine (4VP) on polyphosphates and subsequent hydrolysis and treatment of hydrolysate with aq.…”
Section: -Suggested Explanationssupporting
confidence: 80%
“…Synthesis and reactions of alkyl-, aralkyl-, and heteroalkylpyridines The alkylations of 2and 4-picoline, which have been studied by Chichibabin and coworkers (84, page 467; 328), have received much attention in recent years. Thus, 2-picoline (50,88,134,139,196,197,513,571,572,755,822,823,881) and 4-picoline (50,88,139,196,197,210,755,772) have been treated with alkyl halides (50,88,139,196,513,571,572,755,777), olefinic halides (134), dialkylaminoalkyl halides (196,197,823), alicyclic halides (210, 822), 2-thenyl halides (822), haloethers (197), and haloacetals (881) A few of the alkylation studies have given especially interesting results. Brody and Bogert (134) have alkylated 2-picoline with 11-chloro-l-undecene, and, depending on reaction conditions, have obtained one of the isomeric 2-alkylpyridines indicated in the following scheme: Chichibabin (195,196) found that significant amounts of dialkylated products are formed when 2-picolylsodium is treated with alkyl and aralkyl halides.…”
Section: Zx Zxmentioning
confidence: 99%
“…Compound IV appears as a higher vinylog of stilbestrol; however, a shift of the ethyl groups in IV gives a completely inactive substance, as in V. IV corresponds in type to the equally active 3-(p-hydroxyphenyl)-4-propyl-7-hydroxycoumarin (6) and to the cinnolines recently described by Komfeld (7). 2,6-Dipropylpyridine was obtained from II and ethyl bromide, in analogy to Wibaut and Beets' synthesis of ß-(2-pyridyl)propionaldehyde acetal (8). Its ability to condense with p-hydroxybenzaldehyde is considerably greater than that of 2,6-lutidine, to judge from the relatively good yield of V (see below).…”
mentioning
confidence: 94%